Reforming Employment Protection Legislation in France - Zhou, Jianping (IMF Working Papers; Working Paper ;, 2006)
Over the last 15 years, the reforms of employment protection legislation (EPL) in European countries have mainly eased hiring and firing restrictions for temporary employment while leaving the strict EPL provisions for regular or permanent contracts unchanged. Recent reforms in France follow this pattern. Using a search-matching model, we argue that this type of partial reform is inefficient: easing restrictions on temporary jobs fosters both job creation and job destruction, but strict EPL discourages both. The overall impact on equilibrium unemployment is thus ambiguous, depending on the characteristics of the specific labor market. Simulations of the model, calibrated for the French labor market, suggest that the job destruction effect is stronger, thus raising the unemployment rate.